Inclusion strategies in President El Sissi's discourse in context of election campaigns - Abdelhafiz, Ihab (AUC Knowledge Fountain, 2019)
The goal of this study is to investigate how President Abdelfattah El Sissi used pronouns as well as different alternatives of the word “Egypt” as a discourse strategy to add the sense of inclusion in the context of election campaigns. Group orientation (i.e. inclusion) is of the strategies commonly used in political speeches (Hicks, 2005). Several theories relating to Critical Discourse Analysis (CDA) have been introduced to help understand political speeches beyond the surface level. For the purpose of this study, which includes the text, discourse practices and socio-political context, has been employed. The sample used for this study was downloaded from YouTube and includes two TV interviews with President El Sissi, one before 2014 elections and the other before 2018 elections. The study sought to answer two questions; one on how El Sissi used the collective pronouns ʔeḥna and naḥnu (we) as opposed to his use of the personal pronoun ʔana (I) to add as sense of group orientation; and the other is on how he used the word “Egypt” and other alternatives like “homeland” and “the country” for the same purpose of expressing solidarity with people. Results show that he has successfully used the pronouns as well as the different alternatives of “Egypt” in both interviews to gain people’s support in elections.